Trial of intraoperative cell salvage versus transfusion in ovarian cancer (TIC TOC): a multi-centre randomised controlled feasibility study. (1st November 2019) - Galaal, K; Vickery, J; Lopes, A; Pritchard, C; Barton, A; Wingham, J; Elsa Marques, EM; Palmer, J; Ralph, C; Fauld, J; Ewings, P
Abstract : Introduction/Background: Ovarian cancer is the leading cause of death from gynaecological cancer, with more than 7000 new cases registered in the UK in 2014. Standard treatment includes surgical resection of all macroscopic tumour, followed by chemotherapy. Surgery can be extensive and associated with substantial blood loss which is conventionally replaced with a donor blood transfusion. While often necessary and lifesaving, the use of donor blood is associated with increased risks of complications and adverse surgical outcomes. Intraoperative cell salvage (ICS) is a blood conservation strategy in which red cells collected from blood lost during surgery are returned to the patient thus minimising the use of donor blood. The aim of this feasibility study was to assess whether ICS is a safe alternative to blood transfusion and if a larger, fully powered trial can successfully be planned and delivered. Methodology: This is a randomised, controlled multi-centre feasibility trial conducted in four UK acute NHS hospitals over 12 months. Adult women requiring primary or interval surgery for suspected ovarian cancer were eligible for the trial if CT scan evidence supported FIGO stage III/IV ovarian or primary peritoneal cancer. Participants were randomised 1:1 ratio to receive either intra-operative cell salvage (ICS) reinfusion or donor blood transfusion intra-operatively, with stratification by study site. Results: 173 women were approached, and 59 took part. In the ICS group, 16 (62%) of the 26 participants received ICS reinfusion. In the donor blood group, 14 of the 29 (48%) received donor blood. Twenty-two (40%) participants (9 ICS, 13 control) experienced infections, mainly wound, urinary tract or chest. Six participants died (2 ICS, 4 control) were all due to disease progression. Conclusion: We have demonstrated that ICS is safe and acceptable alternative to blood transfusion in ovarian cancer surgery. Further larger randomised trial is needed to determine the long term outcomes. Disclosure: Nothing to disclose.